Effects of pore fluids on methane sorption in the Lower Bakken Shales, Williston Basin, USA. (15th December 2020) - Tang, Xuan; Zhang, Tongwei; Zhang, Jinchuan; Sun, Xun; Wu, Chenjun; Jin, Zhijun
Highlights: Reduction of CH4 sorption capacity of shale depends largely on the types of pore fluids. The effect of pore fluids on CH4 sorption capacity increases as the order: water < mobile oil < asphaltene. The OM–hosted pores are preferentially coated by asphaltenes, then by the mobile oil. The clay-mineral-hosted pores are preferentially occupied by water. Pyrobitumen formation leads to significant increase of the sorption sites. Abstract: Compositional variation and distribution of pore fluids (water, oil, and asphaltenes) as a function of thermal maturity can greatly affect methane sorption in organic-rich shales. Five Lower Bakken organic-rich shale samples with varied thermal maturity from marginal maturity to oil-to-gas cracking were used in this study to assess this effect. Pore fluids were extracted from samples at four sequential stages: as–received, oven–dried, pentane–extracted, and dichloromethane–extracted; Four aliquots for each sample were used to quantify the effect of water, mobile oil, and asphaltenes on gas sorption. CH4 sorption isotherms were measured at 35 °C, 50 °C, and 65 °C. The results show that presence of pore fluid reduces the CH4 sorption capacity of shale, and the extent of this reduction depends largely on the types of pore fluids. The reduction of CH4 sorption capacity basically follows a linear correlation with moisture content. The effect of mobile oil is 4–5 times greater than that of water. Asphaltenes have no effect on methane sorption capacity for the marginally mature–mature samples but cause a drastic decrease of sorption capacity at the early oil–to–gas cracking. The surfaces of OM–hosted pores are probably coated by asphaltenes, while mobile oil is distributed in the center of the pores, and water mainly occupies the clay-mineral-hosted pores. The sorption sites will increase significantly once oil cracking to gas starts, which is probably associated with pyrobitumen formation. The affinity of CH4 for sorption on pyrobitumen is stronger than that on residual kerogen.